Mental health policy in Britain / Anne Rogers and David Pilgrim. - Rogers, Anne (Palgrave, 2001)
With Mental Health Policy in Britain, Anne Rogers and David Pilgrim present an introduction to the debate regarding the management of mental health services in Britain.